Shake table testing of a miniature steel building with ductile‐anchor, uplifting‐column base connections for improved seismic performance. (15th November 2018) - Trautner, Christopher; Hutchinson, Tara; Grosser, Philipp; Piccinin, Roberto; Silva, John
Summary: Previous research has demonstrated that uplifting‐column or rocking building systems may exhibit improved seismic performance, including reductions in total base shear and decreased residual drift, when compared with systems rigidly connected to the foundation. These beneficial effects may be due to lengthened periods, activation of rocking modes, and energy dissipation of base fuse elements. In the current work, several configurations of a miniature steel building with different combinations of base connection and traditional superstructure fuse strength and stiffness were subjected to identical earthquake motions to evaluate differences in demands and performance. The uplifting base connections incorporate highly ductile concrete anchors with long stretch lengths, allowing robust connection performance and easy replacement of damaged connection elements following the seismic event, an advantage over previously tested systems. Testing and dynamic numerical analysis indicates that ductile anchor uplifting systems may reduce total base shear by over 20%, as well as reducing residual structural drift by more than 80%.